Splitting of flight dynamics equations by using statistical rating - Касьянов, В. А.; Ефремов, С. Г. (Proceedings of National Aviation University (archive), 1999)
Given is the division of linearized fourth-measured system of equations describing aircraft longitudinal motion in two subsystems. This new model contains less parameters to be identified. There are several different transformations necessary to solve division problem named above. It is shown that the application of statistical analysis of residual variances of parameter estimations permits to select most suitable transformation